Determining the most important game-related statistics in Euroleague basketball competitions: A five-year follow-up - İlkay Doğan; Berk Yılmaz; Özkan Işık (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to investigate the game-related statistics in the Play-Off and Final Four rounds of the Euroleague basketball competitions held between 2014 and 2018. In the study, the game-related statistics of 60 teams that participated in the Euroleague Play-Off and Final Four rounds between 2014 and 2018 were evaluated. The independent samples t-test was used to compare the game-related statistics of the two groups. The linear discriminant analysis was used to determine the important game-related statistics between the teams that qualified and those that were eliminated. The results of the study showed that there was a statistically significant difference between the game-related statistics of the two groups in the Play-Off competitions. This difference was seen in the free throw percentage, fouls committed, and performance efficiency scores. As a result of the discriminant analysis, it was found that foul, three-point field-goal percentage, performance efficiency score, turnover, free-throw percentage, and two-point field-goal percentage are important game-related statistics in qualifying the Play-Off round. When the game-related statistics of the two groups in the Final Four were compared, it was seen that only three-point field-goal percentage was an effective variable in becoming the champion. According to the results of the discriminant analysis, turnover, defensive rebound, and total rebound are important game-related statistics to being an Euroleague champion. In conclusion, it is thought that being the Euroleague champion in the Euroleague, it is necessary to have a lower number of turnovers and a defensive game.